The Vienna convention on civil liability for nuclear damage: past, evolution and perspectives - Jakub Handrlica; Marianna Novotná (Juridical Tribune, 2018)
The article remains the 55th anniversary of the adoption of the Vienna Convention on Civil Liability for Nuclear Damage in 1963. As an instrument of international law adopted to tackle the issues of liability and compensation of damages arising from incidents in nuclear installations, the Vienna Convention currently provides for liability framework in 40 Contracting Parties (Installation States) worldwide, establishing – inter alia – a liability framework covering most States of the former Eastern bloc. The purpose of the work is to analyse developments of the Vienna Convention, especially its gradual acceptance among the international community of States in the last decades. Further, the article points out further developments in the field of nuclear liability, in particular the adoption of the Joint Protocol, which established a virtual bridge with another liability regime, provided in the States of Western Europe by the Paris Convention. Also, the article deals with the Protocol of 1997, adopted in order to strengthen the liability framework established by the Vienna Convention. Facing the developments of the last 55 years, the Vienna Convention is to be considered as a successful international treaty. It was able to attract the executives of several Central and Eastern European States, many of which represent major nuclear countries of the region. Further, the specific principles, established by the Vienna Convention, have been accepted as pillars of the legal framework of the peaceful uses of nuclear energy. At last, but not at least, the Vienna Convention represents an instrument, being able to connect this region in the future with other regions, intending for future development of nuclear industry.